2020
DOI: 10.1248/bpb.b20-00221
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast Differentiation Is Suppressed by Increased <i>O</i>-GlcNAcylation Due to Thiamet G Treatment

Abstract: Osteoclasts are the only bone-resorbing cells in organisms and understanding their differentiation mechanism is crucial for the treatment of osteoporosis. In the present study, we investigated the effect of Thiamet G, an O-GlcNAcase specific inhibitor, on osteoclastogenic differentiation. Thiamet G treatment increased global O-GlcNAcylation in murine RAW264 cells and suppressed receptor activator of nuclear factor-κB ligand (RANKL)-dependent formation in tartrate-resistant acid phosphatase (TRAP)-positive mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
(29 reference statements)
1
9
0
2
Order By: Relevance
“…These studies also showed that O-GlcNAcylation occurs in a cell lineage-specific manner during cell differentiation. [12][13][14][15][16] The levels of glucose uptake and utilization are relatively high in pluripotent stem cells, and their levels change as the cells begin to differentiate. 15 Changes in glucose uptake and utilization levels also result in various global O-GlcNAc levels during differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…These studies also showed that O-GlcNAcylation occurs in a cell lineage-specific manner during cell differentiation. [12][13][14][15][16] The levels of glucose uptake and utilization are relatively high in pluripotent stem cells, and their levels change as the cells begin to differentiate. 15 Changes in glucose uptake and utilization levels also result in various global O-GlcNAc levels during differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that OSMI-1 can promote tumor cell apoptosis and has certain prospects for cancer treatment [ 39 , 40 ]. It has been shown to be negatively regulated in osteoclasts [ 41 ] and positively regulated during embryonic differentiation [ 42 ] and in corneal epithelial cells [ 43 ]. In this study, using in vitro experiments, we proved that the application of OSMI-1 to inhibit the function of OGT can improve the degree of damage to lung epithelial cells caused by hyperoxia, enhance cell metabolism and proliferation, decrease apoptosis, and promote cell cycle rates.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on the role of O-GlcNAcylation in osteoclasts contradict a few previous reports. For example, increased O-GlcNAcylation by an Oga inhibitor, O-(2-acetamido-2deoxy-d-glucopyranosylidene) amino-N-phenylcarbamate (PUGNAc), or a glucosamine treatment in Raw264.7 cells inhibits osteoclast differentiation and activity [48][49][50]. This discrepancy could be due to the different cellular contexts and the off-target effects of the different treatments; however, this ironical observation reminds us of the "optimal zone" of O-GlcNAcylation [10].…”
Section: Discussionmentioning
confidence: 99%